Analysis of the Impact of Covid-19 Pandemic on the Economic Condition of Wonogiri - Aullia, Kharimah; Sunariya, M. Iqbal Taufiqurrahman (Universitas Muhammadiyah Surakarta, 2021)
Coronavirusi Diseasei or commonly known as Covid-19 which attacks the respiratory system, severe lung infections and causes death. The Covid-19 virus in several regions continues to increase, this of course causes economic tension in various parts of Indonesia, one of which is Wonogiri Regency. The purpose of this study was to determine the impact of the Covid-19 pandemic on the economy of a region. This study uses GRDP data in Wonogiri Regency in 2016-2020, data processing uses the formula for the rate of economic growth and is analyzed using a comparative descriptive method. Based on research results, the COVID-19 pandemic caused a very sharp decline in the economic sector, the annual GRDP decreased by 3.25%. The economic growth rate of Wonogiri Regency decreased from 4.88% in 2019 down to -1.63% in 2020.